Prognostic Value of Serum 1,5-anhydroglucitol Levels in Patients with Acute Myocardial Infarction - Yijia Wang; Ruiyue Yang; Yanan Zhang; Zhe Wang; Xinyue Wang; Siming Wang; Wenduo Zhang; Xue Yu; Jun Dong; Wenxiang Chen; Fusui Ji (Reviews in Cardiovascular Medicine, 2022)
Background: Diabetes mellitus is a major risk element for cardiovascular disease. In the present study we investigated whether 1,5-anhydroglucitol (1,5-AG), a new marker for glucose monitoring, can predict patient outcome following acute myocardial infarction (AMI). Methods: A total of 270 AMI patients who underwent coronary angiography (CAG) at Beijing Hospital from March 2017 to 2020 were enrolled in this prospective cohort study. The serum 1,5-AG concentration and biochemical indicators were evaluated prior to CAG. Cox regression analysis was used to investigate the relationship between 1,5-AG levels and major adverse cardiovascular and cerebrovascular events (MACCEs), and with all-cause mortality. Results: During the median follow-up period of 44 months, 49 MACCEs occurred and 33 patients died. The 1,5-AG level was significantly lower in the MACCEs group than in the MACCEs-free group (p = 0.001). Kaplan-Meier analysis also revealed that low 1,5-AG levels were associated with MACCEs (p < 0.001) and with all-cause mortality (p = 0.001). Multivariate analysis showed that low 1,5-AG (≤8.8 μg/mL) was an independent predictor of MACCEs (hazard ratio (HR) 2.000, 95% confidence interval (CI): 1.047–3.821, p = 0.036). However, 1,5-AG was not a significant predictor for all-cause mortality in AMI patients (p > 0.05). Conclusions: Low 1,5-AG levels can predict MACCEs in AMI patients, but not all-cause mortality. Clinical Trial Registration: NCT03072797